Vocabulary Acquisition via Drama: Welsh as a second language in the primary school setting. Issue 3 (27th May 2019) - Kalogirou, Konstantina; Beauchamp, Gary; Whyte, Shona
ABSTRACT: This paper tests a new method of teaching vocabulary to young second language learners through the medium of drama, specifically the effect of drama teaching techniques on vocabulary acquisition among primary school learners of Welsh. Vocabulary Acquisition via Drama (VAD) is based on principles derived from both process drama and communicative and task-based approaches to language teaching, and involves three phases: pre-drama, drama and post-drama activities. The research design involves two experimental and one control group, and a pre-post-retention test format on three measures of vocabulary acquisition: picture naming, sentence formulation and improvisation tasks. Results show a beneficial effect for VAD. The discussion section of the paper addresses the potential contribution of this approach to teaching second/foreign language vocabulary.